Associations between health-related social capital and oral frailty risk among older adults: A stratified analysis by socioeconomic status in the JAGES longitudinal study - Nanako Tomioka; Yuka Iwata; Yuko Tanaka; Ayuka Yokoyama; Kisaki Kobayashi; Akemi Matsuzawa; Toshiyuki Ojima; Etsuko Tadaka (PLoS ONE, 2026)
Background Although socioeconomic inequalities in oral health persist despite universal dental care, the role of social determinants remains unclear. Social capital may influence oral frailty, but evidence is limited, particularly regarding individual- and community-level social capital and differences by socioeconomic status (SES). This study examined these associations among community-dwelling older adults. Methods We analyzed longitudinal data from the Japan Gerontological Evaluation Study (JAGES) collected at baseline (2019) and follow-up (2022), including 31,378 older adults. Social capital was assessed across three domains: civic participation, social cohesion, and reciprocity at individual and community levels. Oral frailty was estimated using a validated predictive model incorporating age, remaining teeth, chewing ability, and swallowing function. Multivariable logistic regression analyses examined associations between individual- and community-level social capital and oral frailty risk, as well as the interaction effects of social capital, stratified by SES, on oral frailty risk across SES groups. All models were adjusted for potential confounders, including sex, age, education, household composition, and chronic conditions. Results Over three years, 21.6% of participants developed oral frailty risk, with a higher incidence among low-SES participants (24.6%) than among high-SES participants (19.9%). At the higher individual level, higher health-related social capital and social cohesion were significantly associated with lower odds of oral frailty risk across SES groups. Higher civic participation was also associated with lower oral frailty risk across SES groups, with a stronger association observed among low-SES participants. At the community level, higher civic participation was associated with lower oral frailty risk in the overall sample and among low-SES participants. A significant interaction between SES and individual-level civic participation was observed, while no significant interactions were found for other social capital measures. Conclusions Individual-level health-related social capital was associated with a lower risk of oral frailty among older adults. Furthermore, the inverse association between civic participation and oral frailty was stronger among individuals with low socioeconomic status, suggesting that promoting social participation may be a promising strategy for reducing socioeconomic inequalities in oral frailty.